Leveraging operational use data to inform the systems engineering process of fielded aerospace defense systems - Eddy, Amy, author; Daily, Jeremy, advisor; Marzolf, Gregory, committee member; Miller, Erika, committee member; Wise, Daniel, committee member (Colorado State University. Libraries, 2023)
Inefficiencies in Department of Defense (DoD) Acquisition processes have been pervasive nearly as long as the DoD has existed. Stakeholder communication issues, funding concerns, large and overly complex organizational structures all play a role in adding challenges to those tasked with fielding, operating, and sustaining a complex aerospace defense system. As legacy defense systems begin to age, logistics and other supportability element requirements may change over time. While research literature supports the evidence that many stakeholders and senior leaders are aware of the issues and the DoD faces the impact those issues cause to mission performance, most research and attempts to improve the performance issues have been focused on high level restructuring of organizations or policy, processes, and procedures. There has been little research dedicated to identifying ways for working level logisticians and systems engineers to improve performance by leveraging operational use data. This study proposes a practical approach for working level logisticians and engineers to identify relationships between operational use data and supply performance data. This research focuses on linking negative aircraft events (discrepancies) to the supply events (requisitions) that result in downtime. This approach utilizes standard statistical methods to analyze operations, maintenance, and supply data collected during the Operations and Sustainment (O&S) phase of the life cycle. Further, this research identifies methods consistent with industry systems engineering practices to create new feedback loops to better inform the systems engineering life cycle management process, update requirements, and iterate the design of the enterprise system as a holistic entity that includes the physical product and its supportability elements such as logistics, maintenance, facilities, etc. The method identifies specific recommendations and actions for working level logisticians and systems engineers to prevent future downtime. The method is practical for the existing DoD organizational structure, and uses current DoD processes, all without increasing manpower or other resource needs.
Keywords: defense; process management; aerospace; systems engineering; operations and maintenance